مستقبل الإتحاد الأوروبي في ظل التحالف الثلاثي الأمريكي البريطاني الأسترالي "AUKUS" - بن دار, كريمة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
تسعى هذه الدراسة إلى الكشف عن أهم التحولات التي يشهدها الإتحاد الأوروبي بعد الخروج البريطاني من أسباب وتداعيات، قد تؤثر على مساره التكاملي في القارة، وإلى معرفة تاريخ العلاقات التي برزت أثناء إنضمام بريطانيا له، وإعطاء أهم السيناريوهات التي يمكن أن يمر بها مستقبل الإتحاد في ظل هذا الخروج، الذي قد يزعزع التركيبة التكاملية لهذه التجربة ويدمر علاقات دول الإتحاد، كما يمكن أن يكون حافز رئيسي لخروج دول أخرى من الإتحاد الأوروبي.ومحاولة الكشف عن العلاقات الجديدة مابين التحالف الثلاثي AUKUS"". الذي برز بعد خروج بريطانيا مباشرة منه والذي كان في سبتمبر 2021،من خلال الاتفاقية التي أبرمتها بريطانيا مع كل من الولايات المتحدة الأمريكية و استراليا،في الجانب الأمني والدفاعي . Abstract: This study seeks to reveal the most important transformations that the European Union is witnessing after the British exit from the causes and repercussions, which may affect its integration path on the continent, and to know the history of the relations that emerged during Britain’s accession to it, and to give the most important scenarios that the future of the Union can go through in light of This exit, which may destabilize the integrative structure of this experience and destroy the relations of the countries of the Union. It could also be a major catalyst for the exit of other countries from the European Union.and the study of the new relations between the triple alliance. Which emerged immediately after Britain’s exit from it, which was in September 2021, through the agreement concluded by Britain with both the United States of America and Australia, in the security and defense .